As pequenas e médias empresas inovadoras do estado do Ceará - estudo das empresas incubadas pelo PADETEC - Silva Filho, Ludgero Simeão da (2007)
Brazil’s incubator companies play an import role in the national innovation system, as it integrates research and university institutions with the business world. The contribution of the incubator companies to the innovative companies become more relevant to local innovation systems since it facilitates the innovation process and strengthens the local production system. In Ceará, the experience of the incubator Parque de Desenvolvimento Tecnológico (PADETEC), has been considered a success case as a fomenting institute for innovative companies. This dissertation aims to analyze the financial sources of incubated and graduated companies of PADETEC, emphasizing the contribution of risk capital in the context of the of the applied incubation model. Thus, from documental analyses and from the companies in regards to their products and processes, as well as market performance, considering the aspects of the financing and earnings distribution, an institutional assessment of the incubator was made for its existing period. The information regarding the incubated and graduated companies was collected through a questionnaire. The research shows that small and medium companies compose the dominating group. The results show that because of it’s relevance to the national innovation system, PADETEC is considered by the companies as an incubator essential to the development of their products and processes, but it still does not posses the financial recourses to facilitate the passage from incubated company to graduated company. As for risk capital, it is not clear how this modality of financing decisively contributes to the success of the innovative entrepreneurship, even if a share of the financing comes from own capital or borrowed capital is confirmed. It concludes that when PADETEC’s graduated companies reach the market, they develop and continue with their innovative capacity.